Pengaruh CASA, FDR, CAR, dan Inflasi terhadap ROA pada Bank Umum Syariah di Indonesia - Liana Oktaviani Syahrir; Ade Ali Nurdin; Hanifa Khoirunnisaa Heryanto; Mochamad Edman Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Sharia Commercial Banks in Indonesia have the largest share of assets compared to Sharia Business Unit and Sharia Rural Bank. This shows that the level of trust of the Indonesian people is higher in Islamic Commercial Banks. This study aims to determine the effect of bank financial performance factors seen from financial ratios, including CASA, FDR, and CAR as well as macroeconomic variables, namely Inflation on ROA at Islamic Commercial Banks registered with the OJK. The type of data used is secondary data in the form of annual reports from the official website of each Islamic Commercial Bank and inflation from the BPS. The research method used is quantitative-descriptive with path analysis model through a data processing applications, namely WarpPLS 7.0. The results show that the CASA and CAR variables have a positive and significant effect on ROA. While the FDR and Inflation variables have no effect on ROA.